2006
DOI: 10.1073/pnas.0607207103
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of hippocampal neurogenesis impairs contextual fear conditioning and synaptic plasticity in the dentate gyrus

Abstract: Although hippocampal neurogenesis has been described in many adult mammals, the functional impact of this process on physiology and behavior remains unclear. In the present study, we used two independent methods to ablate hippocampal neurogenesis and found that each procedure caused a limited behavioral deficit and a loss of synaptic plasticity within the dentate gyrus. Specifically, focal X irradiation of the hippocampus or genetic ablation of glial fibrillary acidic protein-positive neural progenitor cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

61
843
5
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 924 publications
(916 citation statements)
references
References 44 publications
61
843
5
7
Order By: Relevance
“…Chronic social isolation also exacerbated the effect of another chronic stressor (daily foot-shock for 3 weeks) on the production of new hippocampal neurons (Westenbroek et al, 2004), and precluded the positive influence of short-term running on neurogenesis (Stranahan et al, 2006). Our findings are consistent with these reports, demonstrating that chronic isolation decreased the production of new neurons, which has been implicated in some hippocampal-dependent learning and memory tasks (Shors et al, 2001;Shors, 2004;Saxe et al, 2006). Thus, it can be suggested that chronic isolation-induced reduction in neurogenesis may be involved in the memory impairment in contextual fear conditioning and spatial memory that accompanies this condition.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Chronic social isolation also exacerbated the effect of another chronic stressor (daily foot-shock for 3 weeks) on the production of new hippocampal neurons (Westenbroek et al, 2004), and precluded the positive influence of short-term running on neurogenesis (Stranahan et al, 2006). Our findings are consistent with these reports, demonstrating that chronic isolation decreased the production of new neurons, which has been implicated in some hippocampal-dependent learning and memory tasks (Shors et al, 2001;Shors, 2004;Saxe et al, 2006). Thus, it can be suggested that chronic isolation-induced reduction in neurogenesis may be involved in the memory impairment in contextual fear conditioning and spatial memory that accompanies this condition.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, exposure to acute psychological stressors, such as short-term (3-5 h) isolation, increased hippocampal IL-1 levels and produced memory impairments that were completely blocked by an intrahippocampal injection of IL-1ra (Barrientos et al, 2003(Barrientos et al, , 2004. Stressful conditions, such as social isolation, also influence several aspects of neural plasticity, including hippocampal neurogenesis (Dong et al, 2004;Westenbroek et al, 2004;Stranahan et al, 2006), which is critically important for some hippocampal-dependent learning and memory tasks (Shors et al, 2001(Shors et al, , 2002Saxe et al, 2006;Winocur et al, 2006). We have recently demonstrated that chronic mild stress, as well as chronic administration of IL-1b, markedly reduces hippocampal neurogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…While the Morris water maze task is not influenced by antimitotic treatment 35,43 , newly generated neurons are activated following this task at a higher rate, relative to mature neurons 44 . Similar distinctions have been reported with respect to the role of adult-generated neurons in recognition memory; enhancement of performance on the novel object preference task following environmental enrichment was reversed by systemic treatment with an antimitotic 45 , but spontaneous alternation in the Y-maze, which also involves recognition memory, was unaffected following focal cranial irradiation 35 . Although it remains to be determined whether adult-generated granule neurons make a meaningful contribution to performance on these tasks under baseline conditions, the therapeutically relevant question is whether new neurons can enhance performance following neurodegeneration or injury.…”
Section: Discussionmentioning
confidence: 88%
“…No studies to date have reported an effect of diabetes on learning-induced changes in hippocampal glucose Lowering corticosterone levels in diabetes can restore behavioral function on tasks that recruit both new and mature neurons. While the Morris water maze task is not influenced by antimitotic treatment 35,43 , newly generated neurons are activated following this task at a higher rate, relative to mature neurons 44 . Similar distinctions have been reported with respect to the role of adult-generated neurons in recognition memory; enhancement of performance on the novel object preference task following environmental enrichment was reversed by systemic treatment with an antimitotic 45 , but spontaneous alternation in the Y-maze, which also involves recognition memory, was unaffected following focal cranial irradiation 35 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation